Outcomes of inpatients with severe mental illness: a naturalistic descriptive study - Gabriela L. Nuernberg; Fernanda L. Baeza; Marcelo P. Fleck; Neusa S. Rocha (Brazilian Journal of Psychiatry, 2016)
Objective: To describe and evaluate the response and predictors of remission during inpatient treatment in a psychiatric unit in a general hospital based on symptomatology, functionality, and quality of life (QoL). Methods: Patients were admitted to a psychiatric unit in a tertiary general hospital in Brazil from June 2011 to December 2013 and included in the study if they met two of the severe mental illness (SMI) criteria: Global Assessment of Functioning (GAF) ≤ 50 and duration of service contact ≥ 2 years. Patients were assessed by the Brief Psychiatric Rating Scale (BPRS), the Clinical Global Impression (CGI) Severity Scale , GAF, the World Health Organization Quality of Life Instrument – Abbreviated version (WHOQOL-Bref), and specific diagnostic scales. Results: A total of 239 patients were included. BPRS mean scores were 25.54±11.37 at admission and 10.96±8.11 at discharge (p < 0.001). Patients with manic episodes (odds ratio: 4.03; 95% confidence interval: 1.14-14.30; p = 0.03) were more likely to achieve remission (CGI ≤ 2 at discharge) than those with depressive episodes. Mean length of stay was 28.95±19.86 days. All QoL domains improved significantly in the whole sample. Conclusion: SMI patients had marked improvements in symptomatic and functional measures during psychiatric hospitalization. Patients with manic episodes had higher chance of remission according to the CGI.